Hubungan Insomnnia Dengan Motivasi Belajar pada Mahasiswa Sekolah Tinggi Ilmu Kesehatan Guna Bangsa Yogyakarta - Eni Purwaningsih; Tri Prabowo; Gaudensius F.B. (LPPM STIKES Guna Bangsa, 2014)
Background: Insomnia is difficulty starting and maintaining sleep which is one of the most common sleep disorders experienced by students. Lack of sleep can disrupt the learning motivation, innovative thought processes, flexible decision-making process and some other cognitive functioning, we know that students must have a strong motivation to learn as well as critical and innovative in the lesson and complete the task during the lecture. The initial data results of interviews with 60 students Guna Bangsa School Of Health Sciences Yogyakarta had obtained 32 students insomnia in last for 1 month. From 32 students who experience insomnia, 25 students said that during the day feel sleepy and tired easily and become lazy to learning. Aim: The aim of this research is to know the relationship of insomnia with studentlearning motivationin Guna Bangsa school of health sciences Yogyakarta. Method: Research using analytic survey approach and cross sectional design. Analysis data using Chi Square. Location of research in Guna Bangsa school of health sciences Yogyakarta with the number of respondents 90 students. Result: The incidence of insomnia was high, 65.6% of total respondents.Students learning motivation was low with the number of students who have low motivation as much as 58,9% of respondents. Based on the results of statistical analysis with the SPSS program obtained from the Chi Square value of 37.538 and p-value <0.1 (0,0001). Conclusion: There was significant relationship between insomnia and the learning motivationof studying Guna Bangsa school of health science Yogyakarta.